Excessive Adjectives with the Multiple Affixations pa-hu in Toba Batak - Ambarita, Esron; Panggabean, Himpun; Sembiring, Elita Modesta (Journal of Applied Linguistics, 2025)
The objectives of this study was to investigate phonological conditioning of the multiple affixations pa-hu in Toba Batak. The method of this study is descriptive qualitative approach to describe Toba Batak phenomena deeply. While multiple affixations have been widely examined in Indonesian language  and in other regional languages, its manifestations in Toba Batak remain largely unexplored. Therefore, this study fills this gap. The findings reveal four distinct categories of phonologically conditioned allomorphs of the multiple affixations pa-hu in Toba Batak with the following requirements: (1) if the root adjective ends in sound [k], [n], or [ŋ], the multiple affixations pa-hu appear as [pa-ku]; (2) if the root adjective ends in sound [m] or [p], the multiple affixations pa-hu appear as [pa-pu]; (3) if the root adjective ends in sound [s], the multiple affixations pa-hu appear as [pa-su]; and (4) if the root adjective ends in sound [t], the multiple affixations pa-hu appear as [pa-tu]. The implications highlight the need to protect regional languages like Toba Batak in the face of globalisation and reach applicable domains like cultural revitalisation. Thus, this study advocates for more research on under-represented languages by bridging the gap between theoretical linguistics and real-world conservation initiatives. Keywords: Excessive adjectives; Multiple affixations; Grammatical functions, Grammatical meanings; Lexical meanings